PENGARUH KOMBINASI KOMPOS TANDAN KOSONG KELAPA SAWIT DENGAN PUPUK NPK PADA MEDIUM PODZOLIK MERAH KUNING TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Khoiril Arifin; Sukemi Indra Saputra; Murniati ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The aim of this research is to identifity the effects and to get the best dosage of TKKS compost combination with NPK fertilizer in red-yelow podzolic medium for cocoa seeds growth varieties forestero the age of 4 months. This research was conducted at the experimental garden of Agriculture Faculty, University of Riau, Bina Widya street KM 12,5 Pekanbaru. This research arranged experimentally using Completely Randomized Design (CRD), with some treatment dosage combination of TKKS compost with NPK fertilizer (P) consist of: P1=37.5 g Compost + NPK 7.5 g, P2= 37,5 g Compost + NPK 11.25 g, P3= 37,5 g Compost + NPK 15 g, P4= 75 g Compost + NPK 7.5 g, P5= 75 g Compost + NPK 11.25 g, P6= 75 g Compost + NPK15 g and consist of 3 replication. Data were analyzed statistically using variety of analysis and further test followed by Duncant’s test at 5 % level. Parameters observed were the seeds height, number of leaves, stem diameter, leaves widht, root width ratio, dry seeds weight, NPK fertilizer efficiency and it relation with dry seeds weight. The result show by giving some treatment of TKKS compost combination with NPK fertilizer on medium podzolic red-yellow on cocoa seeds growth varieties forestero the age of 4 months not reveal significantly to all observed. Giving P1 tretment tend to produce better growth of cocoa seeds. It is seen from seeds height, stem diameter and dry seeds weight. Giving P3 treatment gave the largest efficiency of using NPK fertilizer to 46.113%. Keyword: TKKS compost, NPK fertilizer, Red-yellow podzolic medium, cocoa seeds